US and China’s Foreign Direct Investment (FDI) in Bangladesh in the Age of Indo-Pacific Strategy: : Trends and Patterns - Hasan, Kamrul (The Jahangirnagar Review, 2025)
US and China’s competition is manifested in number of arenas ranging from trade, investment, diplomacy, and politics to security dimension. This competition results in forming several international platforms, frameworks, and institutions such as Belt and Road Initiative (BRI) and Indo-Pacific Strategy (IPS), Indo-Pacific Economic Framework, and Free and Open Indo Pacific etc. Competition between the rising China and USA in the Indo-Pacific region offers new opportunities for small states and challenges as well. Like other small states, there emerges many potentials and encounters for Bangladesh too. Being located in the hotspot of Indian Ocean region, Bangladesh has been successfully able to attract the attention of global and regional economic powerhouses. These development leads to competition among big powers, especially the USA and China, for investment in Bangladesh. In this emerging economic and geopolitical competition between the two major powers, this study, therefore, attempts to gauge the trend and pattern of investment in Bangladesh from both nations. By measuring foreign direct investment (FDI), particularly the report investigates if the competition between the two rival powers impacts the flow of investment over the last decade (2012-2023) in Bangladesh. The study has a great deal of importance because the smooth flow of FDI is one of the keys to economic growth and employment generation. Thus, exploring the trend and pattern of FDI inflow in Bangladesh is substantially significant and relevant. The study provides with a comparative view between two great powers in terms of FDI investment in Bangladesh market, for instance, which industry the transnational corporations (TNCs) from both nations choose the most to invest in, what is the amount, trend and pattern etc. The report finds that there is a distinct increasing trend in the flow of FDI from both economies which might be attributed to the big power’s competition in the region. The report further discloses that, in Bangladesh, US investment is much larger than those of China, and US is the highest contributor economy with regard to FDI. The significant point is that the trend in the flow of FDI from the USA and China is quite similar, both FDI provider show experience of fluctuation (2014-2022). Although US led initiative (for example IPS) is found to be late-comer compared to that of Chinese BRI, competition between the two major powers is noticeable from 2014. Additionally, US investment goes mainly for primary industry, while Chinese TNCs target primarily tertiary industry such as power generation. Although their target industry is somewhat different but overall investment shows a competition which results in increasing amount of FDI in Bangladeshi market. The article is primarily based on the data compiled from Bangladesh bank annual report on FDI and external debt. One of the major pitfalls of the paper is that it has been drawn from a single data source which is Bangladesh Bank, so data triangulation to boost the data accuracy is absent. With robust data from multiple sources, further research can be done in investigating why US TNCs mainly bid for natural resources and Chinese investors for power generation.